The Trial of Jesus and the Interpretation of Psalm cx - Linton, Olof (New Testament studies, 1961)
The question of the High Priest: ‘Art thou the Christ, the Son of the Blessed?’, and the answer of Jesus, mark the culmination of the trial of Jesus. At least this is how it has generally come to be regarded among Christians. This conception, however, is supported by the accounts of Mark and Matthew only. In John we have neither question nor answer. In Luke we have the question, but it is not asked by the High Priest himself; but by the chief priests and scribes (xxii. 6). Furthermore, in Luke the single question in Mark and Matthew: ‘Art thou the Christ, the Son of God?’ is divided into two questions: first, ‘Art thou the Christ?’, and then, ‘Art thou then the Son of God?’ Moreover, the crime of Jesus in Luke is not described as ‘blasphemy’.